Medical information systems in the health services - Harrison, Harold (Statistical and Social Inquiry Society of Ireland, 1976)
The Medical Information System administered by the Medico-Social Research Board (HIPE Scheme) has achieved wide acceptance by hospitals since its inception in 1969. The growth of the Information System has been extremely rapid - approximately 450 percent since 1970. Again using the number of discharges as the measurement, the coverage of the Information System is at present 70 percent. This figure is expected to show a substantial increase in the near future. Although the information produced is extremely detailed and provides a wealth of statistics about the "medical health" of the country its actual use seems to be mainly limited to research investigations, data for hospital administration, and yearly reviews as to how the nation is (medically) progressing. As I have tried to show in this paper much more use could be made of this nationally important Information System. The basic inputs of the Information System could be expeditely handled by modern EDP Systems. Putting the data into magnetic tape would reduce much paperwork and provide a means of directly accessing the information to a main frame computer for analysis. In addition I have shown how this basic information could be further processed by the EDP System to provide important internal control data for individual hospitals. Examples drawn from the USA, Holland and Sweden show how EDP Systems can be developed to provide Medical Information Systems of considerable flexibility and power. At the very least, we in Ireland should be examining and debating the merits of such systems for our own use. It would appear that this is being done on only a very limited scale at present.
Read before the Society, 19 February 1976
Keywords: Medical information systems; Health services; Patient confidentiality; Health research; 314.15